2023
DOI: 10.3390/biology12030426
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of the TIR-NBS-LRR Gene Family and Its Response to Fungal Disease in Rose (Rosa chinensis)

Abstract: Roses, which are one of the world’s most important ornamental plants, are often damaged by pathogens, resulting in serious economic losses. As a subclass of the disease resistance gene family of plant nucleotide-binding oligomerization domain (NOD)-like receptors, TIR-NBS-LRR (TNL) genes play a vital role in identifying pathogen effectors and activating defense responses. However, a systematic analysis of the TNL gene family is rarely reported in roses. Herein, 96 intact TNL genes were identified in Rosa chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The rose ( Rosa hybrida ) varieties used in this study were ‘Princess Michael of Kent’ (KT) and ‘Antique Romantica’ (FG), which showed disease resistance and susceptibility, respectively, after inoculation with the M. rosae strain DBE24-1 ( Song et al., 2023 ). Following a previously described inoculation procedure ( Song et al., 2023 ), the leaves of these two varieties were sprayed with conidia of DBE24-1. Additionally, each variety was sprayed with sterile water containing 0.1% Tween-20 as a control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rose ( Rosa hybrida ) varieties used in this study were ‘Princess Michael of Kent’ (KT) and ‘Antique Romantica’ (FG), which showed disease resistance and susceptibility, respectively, after inoculation with the M. rosae strain DBE24-1 ( Song et al., 2023 ). Following a previously described inoculation procedure ( Song et al., 2023 ), the leaves of these two varieties were sprayed with conidia of DBE24-1. Additionally, each variety was sprayed with sterile water containing 0.1% Tween-20 as a control.…”
Section: Methodsmentioning
confidence: 99%
“…FG leaves were divided into six groups, each containing a total of 6–7 leaves from three individual plants, and sprayed with 0.1, 0.5, 1.5, 3, and 6 mg/L EBL and sterile water (as the control). After 1 d, the DBE24-1-derived conidial solution with reduced pathogenicity was applied by spraying, according to a previously described method ( Song et al., 2023 ). As described above, DI was calculated to measure the extent of disease.…”
Section: Methodsmentioning
confidence: 99%
“…https://doi.org/10.17221/127/2023-PPS ance (Pm3b and Pm8), rice blast resistance (Pi64) and cotton verticillium wilt resistance (GbRVd) as some prominent examples (Zhu et al 2021). While, a few studies have reported TNLs in providing resistance against various biotic stress included verticillium wilt resistance (GhDSC1), Diplocarpon rosae resistance (Rdr1), resistance to downy mildew (MrRPV1), resistance to Colletotrichum fructicola causing Glomerella leaf spot (MdTNL1), resistance against phytophthora root rot (GmTNL16) and resistance against Oidium heveae (WRR4B) (Song et al 2023;Zhou et al 2022;Mei et al 2024). In Solanaceae species, only a handful of TNL genes have been reported against pathogens.…”
mentioning
confidence: 99%
“…In Solanaceae species, only a handful of TNL genes have been reported against pathogens. Examples include Gro1-4 and StTNLC7G2 in potatoes against the Globodera rostochiensis Ro1 pathotype and A. solani (Song et al 2023), respectively. To expand the useful gene pool, many reports have identified the TNLs by genome-wide analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation